Соціальна когезія як основа формування молодіжної політики України - Єфіменко, Людмила Миколаївна; Ефименко, Людмила Николаевна; Yefimenko, Liudmyla; Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Ortina, Hanna (My University, 2020)
UK: Актуальність теми обумовлена необхідністю дослідження важливості використання принципів соціальної когезії як основи формування молодіжної політики країни. У статті досліджується важливість використання принципів соціальної когезії для формування демократичного суспільства в умовах сталого розвитку. Представлено бачення щодо спрямованості прояву соціальної політики держави через формування соціаль- ної когезії для досягнення перспективних національних завдань Цілей Сталого Розвитку. Обґрунтовано основні якості соціальної когезії та взаємозв’язку молодіжної державної політики як передумови демократичного процесу для розбудови сталого розвитку суспільства. EN: The actuality of theme is due to the need to study the importance of using the social cohesion principles as a basis for shaping the country’s youth policy. The article examines the importance of using the social cohesion principles for the democratic society formation in conditions for sustainable development. The vision of the direction of the state social policy manifestation through the social cohesion formation to achieve promising national goals of the Sustainable Development Goals is presented. The main qualities of social cohesion and the relationship of youth public policy as a prerequisite for a democratic process for building sustainable development of society are substantiated. The purpose of scientific research is the socio-philosophical reflection of youth public policy as the basis of the society democratic movement in the global change and world development context.
Social cohesion as the basis for the Ukrainian youth policy formation
Keywords: цінності; соціальна когезія; молодіжна політика; демократія; сталий розвиток; values; social cohesion; youth policy; democracy; sustainable development